Evaluating experimentally the viability of employing hybrid nanofluids as an operating fluid in a shell-and-tube heat exchanger - Amr M. Hassaan (Scientific Reports)
Abstract The use of hybrid nanofluids (HNF) in heat transfer applications has become the subject of studies during recent periods. Its ability to transfer heat is superior to single nanofluids, and this has been proven in many research. Shell and tube heat exchanger is one of the most common types and are therefore always under research to improve their performance. This study is a practical study that examines the effectiveness of HNF in their use as operating fluids in shell-and-tube heat exchangers instead of traditional operating fluids. A laboratory heat exchanger was used to complete this study. A group of HNF (MWCNTs- Al2O3/water) was synthesized at different concentration rates ranging from 0.4 to 2%. Tests were conducted for Reynolds values in the range from 2500 to 12,560. By measuring the variables in the tests and calculating some factors the results showed that, in comparison between the use of HNF and distilled water, it was found that there is an increase in the value of the Nusselt number for the HNF over the distilled water in a range of 10- 28.5%. The effectiveness increased when using the HNF by up to 22.7% compared to distilled water. Through experiments, an equation was deduced to calculate the value of the Nusselt number. There is good agreement between the results of this research and previous literature.